Experimental study on monitoring microwave ablation efficacy by real-time shear wave elastography in ex vivo porcine brain - Rui Li; Yukang Zhang; Linggang Cheng; Shuai Zheng; Hongbing Li; Hongxia Zhang; Lijuan Du; Wen He; Wei Zhang (International Journal of Hyperthermia)
Objective: Glioma constitutes the most common primary malignant tumor in the central nervous system. In recent years, microwave ablation (MWA) was expected to be applied in the minimally invasive treatment of brain tumors. This study aims to evaluate the feasibility and accuracy of microwave ablation in ex vivo brain tissue by Shear Wave Elastography (SWE) to explore the application value of real-time SWE in monitoring the process of MWA of brain tissue.Methods: Thirty ex vivo brain tissues were treated with different microwave power and ablation duration. The morphologic and microscopic changes of MWA tissues were observed, and the diameter of the ablation areas was measured. In this experiment, SWE is used to quantitatively evaluate brain tissue’s degree of thermal injury immediately after ablation.Results: This study It is found that the ablation range measured by SWE after ablation is in good consistency with the pathological range [ICCSWEL1-L1 = 0.975(95% CI:0.959 − 0.985), ICCSWEL2-L2 = 0.887(95% CI:0.779 − 0.938)]. At the same time, the SWE value after ablation is significantly higher than before (mean ± SD,9.88 ± 2.64 kPa vs.23.6 ± 13.75 kPa; p < 0.001). In this study, the SWE value of tissues in different pathological states was further analyzed by the ROC curve (AUC = 0.86), and the threshold for distinguishing normal tissue from tissue after ablation was 13.7 kPa. The accuracy of evaluating ablation tissue using SWE can reach 84.72%, providing data support for real-time quantitative observation of the ablation range.Conclusion: In conclusion the accurate visualization and real-time evaluation of the organizational change range of the MWA process can be realized by real-time SWE.